Sanksi Pidana terhadap Pelaku Pedofilia Perspektif Undang-Undang Nomor 17 Tahun 2016 Tentang Perlindungan Anak dan Hukum Pidana Islam - Manik, Jihan Salsabila Rafidah (Asian Journal of Early Childhood and Elementary Education, 2023)
Pedophilia is an outlet for sexual desires by taking underage children as objects. Acts of sexual violence are very disturbing because they can cause long-term physical and psychological trauma, and victims may become perpetrators in the future. Children as the next generation and the embryo of the nation's hopes have the same rights to live, grow and develop optimally and receive legal protection. In order to improve the handling of cases of sexual violence against children, in 2016 the government issued Law Number 17 of 2016 and it was passed as the second amendment to Law Number 23 of 2002 concerning Child Protection. The aim of this research is to find out what the criminal rules and sanctions are according to Law Number 17 of 2016 concerning Child Protection and Islamic Criminal Law and to compare the two rules. This research uses a type of library research (library research) with several approaches, a statutory approach (legislative approach), a comparative approach (comparative approach), and a conceptual approach. The results of this research are criminal sanctions for pedophilia perpetrators according to the law No. 17 of 2016 concerning Child Protection provides legal sanctions in the form of a minimum prison sentence of 5 years and a maximum of 15 years or a fine of Rp. 5,000,000,000.00 (five billion). According to Islamic criminal law, heterosexual pedophiles are subject to sanctions in the form of adultery, for homosexual pedophiles the death penalty, and takzir for pedophiles who do not fulfill several evidentiary requirements. The similarity between the two is that they both impose heavy sanctions on perpetrators, and the only difference is in terms of law enforcement.